Additional Anomalies in Children with Gastroschisis and Omphalocele: A Retrospective Cohort Study - Adinda G. H. Pijpers; Cunera M. C. de Beaufort; Sanne C. Maat; Chantal J. M. Broers; Bart Straver; Ernest van Heurn; Ramon R. Gorter; Joep P. M. Derikx (MDPI AG, 2023)
Background: Congenital abdominal wall defects might be associated with other anomalies, such as atresia in gastroschisis and cardiac anomalies in omphalocele patients. However, in the current literature, an overview of these additional anomalies and potential patient-specific risk factors is missing. Therefore, we aimed to assess the prevalence of associated anomalies and their patient-specific risk factors in patients with gastroschisis and omphalocele. Methods: A mono-center retrospective cohort study between 1997 and 2023 was performed. Outcomes were the presence of any additional anomalies. Risk factors were analyzed via logistic regression analysis. Results: In total, 122 patients were included, of whom 82 (67.2%) had gastroschisis, and 40 (32.8%) had omphalocele. Additional anomalies were identified in 26 gastroschisis patients (31.7%) and in 27 omphalocele patients (67.5%). In patients with gastroschisis, intestinal anomalies were most identified (n = 13, 15.9%), whereas, in patients with omphalocele, cardiac anomalies were most identified (n = 15, 37.5%). Logistic regression showed that cardiac anomalies were associated with complex gastroschisis (OR: 8.5; CI-95%: 1.4-49.5). Conclusions: In patients with gastroschisis and omphalocele, intestinal and cardiac anomalies were most identified, respectively. Cardiac anomalies were found to be a risk factor for patients with complex gastroschisis. Therefore, regardless of the type of gastroschisis and/or omphalocele, postnatal cardiac screening remains important.